Circumventing Novice Teacher Imbroglio in Kenya: A Proposed Mentorship Program - Kailiti, Hellen B. K (IJRDO- Journal of Educational Research, 2017)
Novice teachers, in primary and secondary schools, in Kenya face a myriad of problems and challenges in the early stages of their teaching career. As much as they have gone through the colleges, when they embark on teaching, they realize that they have inadequate knowledge, skills and attributes to handle learners. In most cases, there is little support from other teachers and with time, negative experiences erode the confidence of beginning teachers over time, leading to high attrition rate. Sometimes, beginning teachers a face reality shock as the theories learned during their training do not fit neatly into the real-world teaching practice even for though they have undertaken teaching practice. In the first year of training, many beginning teachers are given responsibilities out of the classroom which they have to undertake, even when they did not learn about the tasks involved. Sometimes, the veteran teachers have less responsibilities and they have time to informally supervise the beginning teachers. Most beginning teachers are enthusiastic about the work but after experiencing frustration and alienation from the veteran teachers, they gradually lack morale and end up having very little achievement as far as learning outcomes are concerned. When teachers are thrust into the profession without proper guidance in place, they struggle on their own to make learners to perform well in exams and other activities. A welldesigned mentorship program can enable teachers to adapt well to the profession and be motivated enough to motivate the learners. This paper conceptualizes a plan for teacher mentoring in Kenya. If adopted, the model can be used to improve the performance of beginning teachers or teachers on new assignments